Cheap Talk in the Classroom: How Biased Grading at School Explains Gender Differences in Achievements, Career Choices and Wages - MECHTENBERG, LYDIA (Review of Economic Studies, 2009)
In this paper, I provide a theoretical explanation for the gender differences in education and on the labour market that are observed empirically in most OECD (Organisation for Economic Cooperation and Development) countries, including the US Within a cheap talk model of grading, I show that biased grading in schools results in (1) boys outperforming girls in maths and sciences, (2) boys having more top and more bottom achievers in maths and sciences than girls, (3) girls outperforming boys in reading literacy, (4) female graduates enrolling in university studies more often than male graduates, (5) the predominance of female students in arts and humanities at the university, (6) the predominance of male students in maths and sciences at the university and (7) the gender wage gap on the labour market for the highly educated.